Efektifitas Pemanfaatan Media Gambar Bergerak dan Video Animasi terhadap Peningkatan Pengetahuan dan Sikap Ibu tentang Gizi Seimbang pada Balita - Christin Angelina Febriani; Dina Dwi Nuryani; Dessy Elviyanti (Politeknik Kesehatan Tanjung Karang, 2019)
The fact that malnutrition occurs during the golden age is irreversible, so more attention is needed in the growth and development of toddler age. This research is aim to find out the improvements of mothers’ knowledge concerning balanced nutrition for children under five before and after intervention by using moving picture and animated video media in Ambarawa public health center working area in Pringsewu district in 2019. Quantitative-quasi-experiment design, with pretest–post-test with the group design approach. The population was 216 respondents and 40 respondents were taken by using proportional random sampling and purposive sampling. Data were analyzed with univariate and bivariate analyses by using the independent t-test. The results showed that the averages of mothers’ knowledge concerning balanced nutrition for children under five before and after using moving picture media intervention were 78.60 and 83.80, and before and after using animated video media intervention were 78.00 and 91.90 with p-value 0.120. The averages of mothers attitude concerning balanced nutrition for children under five before and after using moving picture media intervention were 76.05 and 78.60, and before and after using animated video media intervention were 78.55 and 85.65 with p-value 0.087. Animation media is more effective against increasing the knowledge and attitudes of mothers about balanced nutrition, it appears from the average value of the use of animation media higher than moving images.